Letter : Children of Spanish Miners Residing in England - Edwards, Ebby
1938-10-06 038-0120-002 TELEPHONE: MUSEUM 8886 TELEGRAMS: MINFEDBRIT, WESTCENT, LONDON THE MINEWORKERS' FEDERATION OF GREAT BRITAIN 50, Russell Square, London, W.C.1 6th October 1938. SECRETARY: EBBY EDWARDS Mr. H.V. Tewson, Trades Union Congress, Transport House, Smith Square, London, S.W.1. Dear Mr. Tewson, CHILDREN OF SPANISH MINERS RESIDING IN ENGLAND. Your letter of the 3rd instant addressed to Mr. W. Lawther, Vice-President of the above Federation was considered at a meeting of our Executive Committee held on the 4th instant. I was instructed to write informing you that in the opinion of the Committee they consider the commitment for Basque children is one for not only the whole of the movement but for all who were responsible for bringing the children into the country, and as the miners in various parts of the country are already contributing towards the maintenance of these children, the Committee were unable to accede to your request. Your sincerely, Ebby Edwards Secretary. 292/946/38/120(II)